Capacity and phase stability of metal-substituted α-Ni(OH)2 nanosheets in aqueous Ni–Zn batteries. Issue 9 (12th April 2021) - Kimmel, Samuel W.; Hopkins, Brandon J.; Chervin, Christopher N.; Skeele, Nathaniel L.; Ko, Jesse S.; DeBlock, Ryan H.; Long, Jeffrey W.; Parker, Joseph F.; Hudak, Bethany M.; Stroud, Rhonda M.; Rolison, Debra R.; Rhodes, Christopher P.
Abstract : Incorporating Al 3+ within α-Ni(OH)2 nanosheets provides higher capacity in Ni–Zn cells with phase stability upon cycling compared to the other tested divalent substituents and unsubstituted α-Ni(OH)2 . Abstract : Batteries that offer high specific energy and energy density coupled with improved safety and lower cost will affect applications ranging from electric vehicles, portable electronic devices, and grid-level energy storage. Alkaline nickel–zinc (Ni–Zn) batteries use nonflammable aqueous electrolyte and nonstrategic, low-cost electrode materials; however with a two-electron anode, a cathode that stores more than one electron per Ni atom would increase energy density. Herein, we report the effect of substituting metal ions (aluminium, cobalt, manganese, or zinc) into α-Ni(OH)2, a phase that can accommodate more than one-electron charge storage, but which typically converts to lower-capacity β-Ni(OH)2 upon cycling in alkaline electrolytes. We adapt a microwave-assisted process that expresses α-Ni(OH)2 as a high surface-area nanosheet morphology and find that we retain this morphology with all metal-ion substituents. The series is characterized using scanning electron microscopy, transmission electron microscopy, X-ray diffraction, and Raman spectroscopy. Metal-ion substitution influences aggregate growth, interlayer distance, and vibrational frequencies. We test powder-composite cathodes prepared using the substituted α-Ni(OH)2 series versus zinc sponge anodes in alkaline electrolyte under device-relevant mass loadings and using an intentionally aggressive charging protocol to determine onset voltage for oxygen evolution. The electrochemical charge-storage behaviour is established using galvanostatic cycling and differential capacity analysis. The substituents significantly influence both Ni-centred redox and oxygen-evolution voltages ( vs. Zn/Zn 2+ ). The incorporation of Al 3+ within α-Ni(OH)2 nanosheets provides higher capacity and phase stability compared to the divalent substituents and unsubstituted α-Ni(OH)2 . The presence of ordered free nitrates in the interlayer of Al 3+ -substituted α-Ni(OH)2, not seen with Co 2+ or Mn 2+ substituents, correlates with the improved electrochemical performance.